(3eNJUQ CSeGA GdUMGHIs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3GHf NjQI GdCTgdi PcQg GHf GdcdHi PcQg GHf efOg GdMdci GdCShO (B: (3cGf QGYjkG djghO NjHQ aCSde s
(3BNQgG (B:s
(3ef HGH (B" (3GdeLghdGJ (B" (3hGdZGeOjI GdJi QLeJ (B: (3GdJi bGd QShd Gddg Udi Gddg Ydjg hSde (B" (3dbO JGHJ hOafJ CNQLgG CHh ehSi Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3HgG NQhe hJQbjYs
(3Vef GdeDda GdcJGH CSeGA GdUMGHI hGdUMGHjGJ hQJHg Ydi MQha GdeYLe haQZ ef JCdjag HecI SfI (B817s
(3HBNQgG NW eMeO eQJVi GdRHjOi UGMH JGL GdYQhS Cfg edcgG hCJe bQGAJgG heQGLYJgG ai GdbGgQI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdJGQjNs